2018
DOI: 10.1155/2018/4572989
|View full text |Cite
|
Sign up to set email alerts
|

Mode‐I Metal‐Composite Interface Fracture Testing for Fibre Metal Laminates

Abstract: The main contribution of the present paper is the determination of the mode-I fracture of metal-composite interface region for fibre metal laminates (FMLs). A hybrid DCB configuration is proposed to investigate the mode-I fracture between metal-composite interface using experimental and numerical approaches. A computationally efficient and reliable finite element model was developed to account for the influence of metal plasticity on the measured fracture energy. The results of the experimental and numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…where k I is the slope for Mode-I and k II is the slope for Mode-II; x is the respective temperature based on the required parameter. On the other hand, the value of peak traction stresses is ratioed concerning the fracture toughness ratio between different temperatures based on Equations (13) and (14), where a similar method was used by Qin et al [23] to acquire low and elevated temperature properties.…”
Section: Finite Element Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…where k I is the slope for Mode-I and k II is the slope for Mode-II; x is the respective temperature based on the required parameter. On the other hand, the value of peak traction stresses is ratioed concerning the fracture toughness ratio between different temperatures based on Equations (13) and (14), where a similar method was used by Qin et al [23] to acquire low and elevated temperature properties.…”
Section: Finite Element Modellingmentioning
confidence: 99%
“…The bending and flexural performance of glass laminate aluminium-reinforced epoxy (GLARE) with different varieties of layups were investigated by Li et al [ 12 ] with combined experimental and numerical finite element analyses. Due to the ductile nature of metals, the fracture energy of the metal–composite interface is higher than the actual interface energy due to metal plasticity from bending in Mode-I [ 13 ]. An in-depth finite element analysis on Mode-I and mixed-mode I/II by Zhao et al [ 14 ] found that the interface strength of composite laminates within a certain boundary has minuscule effects on the simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…There is only a small group of published works that investigate the interfacial fracture of joints (or, to be more precise, multi-layered beam-like specimens) consisting of two "non-homogeneous" (i.e., elastically coupled) sub-laminates [7][8][9][10][11][12][13][14]. In this case, studying the various published papers [7][8][9][10][11][12][13][14], we observed that the experimental data were post-processed using different data reduction approaches, from simpler approaches, such as the Euler beam theory or William's global method, to more sophisticated ones, such as Wang and Qiao's [15] approach. In some cases, the utilized data reduction scheme does not consider the elastic coupling effects and thus does not give accurate predictions of the fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The SERRs acquired by both methods were identical for the initial crack length, but by increasing the crack length, the fracture energies estimated by the plate theory surpassed those by the compliance calibration method. In [12], the mode I fracture toughness of the metal/composite interface region of some fiber metal laminates were determined and a finite element model was developed to account for the influence of metal plasticity on the measured fracture toughness. In [13], modified DCB specimens were tested to investigate the mode I fracture properties of an asymmetric metal-composite adhesive joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation